IMPROVEMENT OF CYCLONE INSTALLATION (Web of Discoveries: Journal of Analysis and Inventions, 2025)
Cyclones for cleaning dusty air flow are one of the main equipment for cleaning air from small impurities, fibrous waste, they are widely used in cotton and textile enterprises.